Heavy metals availability and soil fertility after land application of sewage sludge on dystroferric Red Latosol - Rodrigo Santos Moreira; Ronaldo Luiz Mincato; Breno Régis Santos (Ciência e Agrotecnologia, 2013)
Sewage sludge is the solid residue obtained from urban sewage treatment plants. It is possible to use the sludge in a sustainable way as fertilizer and as soil conditioner due to its high levels of organic matter and nutrients. Besides pathogens and volatile organic compounds, the residue may also contain heavy metals which may accumulate and contaminate crops and the food chain. The aim of this study was evaluates the changes in the fertility of dystrophic Red Latosol and in the availability of heavy metals following application of sewage sludge. It was assessed whether organic matter supplied to the soil as large amounts of sewage sludge would decrease availability of heavy metals in the soil due to of insoluble compounds formation. From this, an experiment was carried out in polyethylene pots using lettuce plant for test. Sewage sludge were applied to the soil in concentrations equivalent to 60, 120 and 180 t ha-1, and a control without sludge, in four replicates, in a completely randomized design. The results show that sewage sludge led to an increase of organic matter contents, of the cation exchange capacity (CEC) and of nutrients found in the soil. It also improved plant growth up to a concentration of 120 t ha-1. Availability of heavy metals, however, was reduced in sludge concentrations starting with 120 t ha-1.